2019
DOI: 10.4269/ajtmh.18-0947
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Usefulness of Cytokine and Chemokine Levels in the Cerebrospinal Fluid of Patients with Suspected Tuberculous Meningitis

Abstract: In this study, we investigated the diagnostic utility of the cytokine profile of the cerebrospinal fluid (CSF) and enzyme-linked immunospot (ELISPOT) assays of patients with suspected tuberculous meningitis (TBM). We prospectively enrolled adult patients with suspected TBM, and CSF specimens were analyzed for 18 cytokines/chemokines and soluble programmed death protein 1 (PD-1) and programmed death ligand 1 (PD-L1). Enzyme-linked immunospot assays were performed on mononuclear cells from the CSF (CSF-MCs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Besides, the lack of accessible and timely methods also contributed to a delay in diagnosis and subsequent morbidity and mortality for TBM patients, particularly those in resource-limited settings ( 29 ). Although the potential biomarkers of proteome ( 30 ), metabolome ( 31 ), and transcriptome ( 32 ) have been identified for TBM diagnosis in recent years, these markers have not been sufficiently verified. In this study, we compared the laboratory features including CSF indexes and TBAg/PHA ratio in T-SPOT assay among patients with these two types of meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the lack of accessible and timely methods also contributed to a delay in diagnosis and subsequent morbidity and mortality for TBM patients, particularly those in resource-limited settings ( 29 ). Although the potential biomarkers of proteome ( 30 ), metabolome ( 31 ), and transcriptome ( 32 ) have been identified for TBM diagnosis in recent years, these markers have not been sufficiently verified. In this study, we compared the laboratory features including CSF indexes and TBAg/PHA ratio in T-SPOT assay among patients with these two types of meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies with TB pleural effusion patients, CCL27 levels were significantly higher in PE samples from anergic patients with TPE, compared to those in non-anergic TPE and malignant PE (p < 0.001) (55). Furthermore, recent studies for the suspected cases of tuberculous meningitis (TBM) showed that the upregulated cytokine/chemokine profiles including IL-12p40, IL-13, and MIP-1α as potentially useful adjunctive markers for diagnosis of TBM (56). These data suggest that specific chemokine levels, combined with the known biomarker ADA levels, might be helpful for the diagnosis of extrapulmonary TB.…”
Section: Biomarkers During Extrapulmonary Tb Infectionmentioning
confidence: 94%
“…After independent reviews, 27 studies met the inclusion criteria and were finally included into meta-analysis ( Table 1 and Figure 1 ). The PB-based T-SPOT was performed in 25 studies ( 26 – 35 , 37 – 42 , 44 – 52 ), and the CSF-based T-SPOT was used in 16 studies ( 26 29 , 31 , 32 , 36 – 39 , 41 , 43 , 46 , 48 , 50 , 51 ). Head-to-head comparisons of the diagnostic accuracies of PB T-SPOT against CSF T-SPOT were found in 14 studies.…”
Section: Resultsmentioning
confidence: 99%